PERSEPSI SANTRI TERHADAP PEMBELAJARAN DARING DI LINGKUNGAN PONDOK PESANTREN AL-HASYIMI KABUPATEN PEKALONGAN - Purwita Wulandari; Wirani Atqia (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
Learning with the online method is one of the answers to learning during this corona pandemic. This author's writing wants to see how the response and practice of online learning in Islamic boarding schools is. The research question was formulated: How are the students' perceptions of teaching and learning activities at the Al-Hasyimi Islamic boarding school during the COVID-19 pandemic? And what are the supporting and inhibiting factors for students in teaching and learning activities at the Al-Hasyimi Islamic boarding school during this covid 19 pandemic?. Everyone has a different perception of a condition, be it social conditions or other conditions that exist in society. Perception is a unique interpretation of a situation. Perception is individual, because perception is an integrated activity within the individual, therefore perception can be expressed because of feelings and thinking abilities. This study uses a qualitative research approach by exploring the tendency of many Islamic boarding schools in providing education to respond to the Covid-19 pandemic by clarifying a case study of a pesantren. The case selected here is the students' perception of online learning at the Al Hasyimi Islamic Boarding School, Pekalongan Regency. This study concludes that online learning in Islamic boarding schools does not work because of the students' assumption that gadgets and smartphones provide more harm than benefits for the development of education in Islamic boarding schools. This is the main source of the problem with the stuttering of technology and communication tools in Islamic boarding schools in dealing with online learning during a pandemic like this. This study suggests the need for new policies related to the use of communication technology in Islamic boarding schools. If so far it is still strictly prohibited, in the future certain access is needed so that students (santri) can usecommunication media in developing learning.